AN ANALYSIS OF TEACHER'S QUESTIONING STRATEGIES IN CLASSROOM INTERACTION - Lestari, Andi Surya; Yasim, Sukmawati; Imansari, Nurul (English Language, Linguistics, and Culture International Journal, 2022)
The purpose of this study was to analyze the questioning strategies used by the teacher in class interaction and the teacher's preference for using questioning strategies. The approach used in this research is qualitative. The subjects of this study were two English teachers at SMPN 5 Majene. The subjects of this study were determined using purposive sampling technique. For data collection in this study used instruments such as classroom observations using checklist observations and video recording and interviews using a voice recorder. The results of this study indicate that the teacher uses knowledge questions and comprehension questions in the classroom. Based on the results of the analysis of this study, the teacher also explained that questioning strategies are very important, especially the teacher uses a questioning strategy to measure the extent of students' understanding and abilities during learning.